MLL leukemia induction by t(9;11) chromosomal translocation in human hematopoietic stem cells using genome editing - Corina Schneidawind; Johan Jeong; Dominik Schneidawind; In-Suk Kim; Jesús Duque-Afonso; Stephen Hon Kit Wong; Masayuki Iwasaki; Erin H. Breese; James L. Zehnder; Matthew Porteus; Michael L. Cleary (Blood Advances, 2018)
Abstract: Genome editing provides a potential approach to model de novo leukemogenesis in primary human hematopoietic stem and progenitor cells (HSPCs) through induction of chromosomal translocations by targeted DNA double-strand breaks. However, very low efficiency of translocations and lack of markers for translocated cells serve as barriers to their characterization and model development. Here, we used transcription activator-like effector nucleases to generate t(9;11) chromosomal translocations encoding MLL-AF9 and reciprocal AF9-MLL fusion products in CD34+ human cord blood cells. Selected cytokine combinations enabled monoclonal outgrowth and immortalization of initially rare translocated cells, which were distinguished by elevated MLL target gene expression, high surface CD9 expression, and increased colony-forming ability. Subsequent transplantation into immune-compromised mice induced myeloid leukemias within 48 weeks, whose pathologic and molecular features extensively overlap with de novo patient MLL-rearranged leukemias. No secondary pathogenic mutations were revealed by targeted exome sequencing and whole genome RNA-sequencing analyses, suggesting the genetic sufficiency of t(9;11) translocation for leukemia development from human HSPCs. Thus, genome editing enables modeling of human acute MLL-rearranged leukemia in vivo, reflecting the genetic simplicity of this disease, and provides an experimental platform for biological and disease-modeling applications.